From 2-methylimidazole to 1, 2, 3-triazole: a topological transformation of ZIF-8 and ZIF-67 by post-synthetic modification. Issue 12 (26th January 2017) - Erkartal, Mustafa; Erkilic, Ufuk; Tam, Benjamin; Usta, Hakan; Yazaydin, Ozgur; Hupp, Joseph T.; Farha, Omar K.; Sen, Unal
Abstract : We report the first examples of the simultaneous non-assisted replacement of ligands and the conversion of topology in MOFs by applying the PSM approach. Abstract : Bridging ligand replacement in zeolitic imidazolate frameworks, ZIF-8 and ZIF-67, by 1, 2, 3-triazole was investigated. A complete substitution of 2-methylimidazole by 1, 2, 3-triazole resulted in a topological transformation of the parent framework from a sodalite (SOD) network to a diamond (DIA) network.